Nutrition: a foundation for development: Why practitioners in development should integrate nutrition - International Food Policy Research Institute; United Nations Systems Standing Committee on Nutrition (International Food Policy Research Institute, 2002)
Nutrition: A Foundation For Development is a compilation of 12 briefs on the latest research findings in nutrition as they relate to other development sectors. The briefs are designed to facilitate dialogue between nutrition and other development professionals. They are organized both as a complete set or as stand-alone briefs that make the case for integrating nutrition into the work of the development community.